Sensory abnormalities and pain in Parkinson disease and its modulation by treatment of motor symptoms - Cury, R. G. (2016)
Pain and sensory abnormalities are present in a large proportion of Parkinson disease (PD) patients and have a significant negative impact in quality of life. It remains undetermined whether pain occurs secondary to motor impairment and to which extent it can be relieved by improvement of motor symptoms. The aim of this review was to examine the current knowledge on the mechanisms behind sensory changes and pain in PD and to assess the modulatory effects of motor treatment on these sensory abnormalities. A comprehensive literature search was performed. We selected studies investigating sensory changes and pain in PD and the effects of levodopa administration and deep brain stimulation (DBS) on these symptoms. PD patients have altered sensory and pain thresholds in the off-medication state. Both levodopa and DBS improve motor symptoms (i.e.: bradykinesia, tremor) and change sensory abnormalities towards normal levels. However, there is no direct correlation between sensory/pain changes and motor improvement, suggesting that motor and non-motor symptoms do not necessarily share the same mechanisms. Whether dopamine and DBS have a real antinociceptive effect or simply a modulatory effect in pain perception remain uncertain. These data may provide useful insights into a mechanism-based approach to pain in PD, pointing out the role of the dopaminergic system in pain perception and the importance of the characterization of different pain syndromes related to PD before specific treatment can be instituted.